The ‘Moros of Mindanao: A Subject of Social Closure - Tomaro, Queenie Pearl Villalon (Journal of Governance and Public Policy, 2019)
The long clamor of the Moro people, an Islamized group in southern Philippines, is not only a clamor that has been systematically ignored but one that is left unresolved and often politicized. This has led to a series of disappointing legal attempts to better the underdeveloped Muslim region through the failed experiment of decentralizing financial resources and political power. In light of this, the paper aimed to analyze the system-rooted social closure that the case of the Autonomous Region of Muslim Mindanao reflects. It is analyzed in the lens of the systematic exclusion apparent in the compiled statistical data from the Philippine Statistical Authority and other scholars. Also, social closure is analyzed by looking into the usurpationary activities undertaken by Moro armed groups to gain access from resources; political and economic. The paper is a qualitative explanatory study which provides an analytical lens to the secondary data gathered from government websites of the Philippines and from scholarly reports and published studies. It was confirmed in the study that the Moro People are socially excluded and some are supporting if not affiliated to the Armed groups fighting the government for a better autonomous region, some even for an independent state for the Moro nation.